Design and experiment of double planet carrier planetary gear flower transplanting mechanism - Zhao, Xiong; Liao, Hongwei; Ma, Xingxiao; Dai, Li; Yu, Gaohong; Chen, Jianneng (International Journal of Agricultural and Biological Engineering, 2021)
At present, there is a lack of miniaturized and highly reliable plug seedling transplanting mechanism in flowerpots planting operation, in order to meet the needs of large displacement and high vertical uprightness for flower transplanting, the paper combined the transmission characteristics of the non-circular gear planetary gear train with the swing flexibility of the cam gear and proposed a double planet carrier planetary gear transplanting mechanism. The linkage of the mechanism performs variable speed rotation relative to the first planet carrier, the linkage serves as the second planet carrier, and the transplanting arm performs variable speed swing relative to the linkage. A mathematical model of a single planetary carrier mechanism was first established using the method of open linkage group solution domain synthesis, then established the kinematic equations of the second planet carrier and the transplanting arm. The two parts are combined to form the mathematical solution model of the proposed mechanism. The initial trajectory was planned according to the trajectory requirements of seedlings planting operation, the non-circular gear pitch curve in the first planet carrier was obtained and the length of the first planet carrier is 120 mm. Then using the key points’ angular deviation between the initial trajectory and the improved trajectory to obtain the cam parameters which driving the transplant arm, consequently determined the length of the second planet carrier is 69.25 mm and the length of the transplant arm is 112.4 mm. Finally, the prototype of the mechanism was manufactured, and the test verified the correctness of the design method of the double planet carrier planetary gear flower potting transplanting mechanism. The transplanting success rate of this mechanism reached 94.43%, and the plug seedlings planted in flowerpots had high uprightness. This research can provide a reference for the automatic development of research on flower transplanting machines.Keywords: flower transplanting, double planet carrier planetary gear mechanism, non-circular, plug seedlingDOI: 10.25165/j.ijabe.20211402.5878Citation: Zhao X, Liao H W, Ma X X, Dai L, Yu G H, Chen J N. Design and experiment of double planet carrier planetary gear flower transplanting mechanism. Int J Agric & Biol Eng, 2021; 14(2): 55–61.